MEDAN CHINESE AND THEIR STIGMA: GRABBING POWER IN MULTICULTURAL SOCIETY - Alkatiri, Zeffry; Waworuntu, Adrianus L. G.; Gani, Fuad; Archellie, Reynaldo de (UI Scholars Hub, 2019)
This article presents the result of a pilot project which seeks to examine the pattern of socio-cultural interaction between the Chinese people and other ethnic groups in the multicultural City of Medan, North Sumatra. The purpose of this article is to examine various obstacles in the pattern of socio-cultural interaction among those two groups of people. This article utilizes both field data and the data obtained from bibliographical references. This qualitative research applies the ethnographical approach and is conducted by observing various activities and behaviors that arise from the pattern of socio-cultural interaction between the Chinese people and other ethnic groups in Medan. From this project, we draw a preliminary conclusion that the Medanese Chinese have established domination over numerous areas of life in Medan by engaging in various socio-cultural activities, both conspicuously and inconspicuously. Such hegemonic tendencies have contributed to creating a negative perception of the Medanese Chinese among other members of the plural society in Medan. In addition to that, the difficulty of Medanese Chinese to assimilate themselves with the local populace only increases the social gap between them and other local communities. These factors constitute challenges for the Medanese Chinese to interact with people from other ethnic groups.